2014
DOI: 10.1038/ng.3046
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the stress-tolerant wild tomato species Solanum pennellii

Abstract: Solanum pennellii is a wild tomato species endemic to Andean regions in South America, where it has evolved to thrive in arid habitats. Because of its extreme stress tolerance and unusual morphology, it is an important donor of germplasm for the cultivated tomato Solanum lycopersicum 1 . Introgression lines (ILs) in which large genomic regions of S. lycopersicum are replaced with the corresponding segments from S. pennellii can show remarkably superior agronomic performance 2 . Here we describe a high-quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
406
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 427 publications
(454 citation statements)
references
References 46 publications
28
406
0
1
Order By: Relevance
“…The tomato whole genome sequence (26) and the S. pennellii genome sequence (27) were searched for SLF coding genes. Candidate genes were annotated using GENSCAN (genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tomato whole genome sequence (26) and the S. pennellii genome sequence (27) were searched for SLF coding genes. Candidate genes were annotated using GENSCAN (genes.…”
Section: Methodsmentioning
confidence: 99%
“…We identified 19 SLF genes (SlSLF-1 to -19) in the S. lycopersicum genome that mapped to the S-locus region on chromosome 1 (SI Appendix). We also searched the S. pennellii accession LA0716 genome sequence (27) using the same Petunia SLF protein to find related proteins. Four additional SLF paralogs (SpSLF-20 to -23) were identified in the S. pennellii genome that were absent from tomato (SI Appendix).…”
Section: Ui11mentioning
confidence: 99%
“…Resequencing confirmed that the S. lycopersicum M82 SlIPMS3 also contains this truncation, indicating that this is a bona fide change rather than a sequence assembly error. Because introgression of the S. pennellii LA0716 region containing this gene has a major impact on acyl chain composition, we attempted to identify the orthologous gene from this accession using available sequence data (Bombarely et al, 2012;Tomato Genome Consortium, 2012;Bolger et al, 2014a). The SlIPMS3 (Solyc08g014230) and S. pennellii (Sopen08g005140) genes are reciprocal best hits, with 97% identity within a large syntenic region comprising 361 collinear genes (see "Materials and Methods").…”
Section: Identification Of a Novel Trichome-expressed Ipms Genementioning
confidence: 99%
“…For reciprocal best match, we performed an all-versus-all BLAST between all annotated S. lycopersicum and S. pennellii proteins (Bolger et al, 2014a) and selected pairs that were reciprocal best hits of each other at E , 1e-10. We determined genome-wide synteny between reciprocal best hits using MCScanX (Wang et al, 2013) using the default parameters.…”
Section: Determination Of Orthologymentioning
confidence: 99%
“…In this respect, the scientific genomic achievements in tomato have allowed fishing in its gene pool and taking advantage of the extraordinary genetic wealth of its wild relatives (Víquez-Zamora et al, 2013;Aflitos et al, 2014). In this way, tomato breeders have been able to find genetic solutions to some biotic and abiotic threats and achieving improvements to cope with unfavorable agricultural environments in a climate change scenario (Bolger et al, 2014;Thapa et al, 2015). On the contrary, up to now in common eggplant, as well as in scarlet and gboma eggplant, the use of wild relatives for the breeding purpose have been negligible and often purely academic .…”
Section: Genome Assembliesmentioning
confidence: 99%